SAA and lipid metabolism in IPF - Vietri, Lucia; d’Alessandro, Miriana; Casolari, Paolo; Monaco, Andrea Lo; Reginato, Mariano; Marchi, Irene; Gatti, Ilaria; Carnevale, Aldo; Rizzo, Ludovica; Bergantini, Laura; Gangi, Sara; Cameli, Paolo; et al. (Archives of Clinical and Biomedical Research, 2025)
Lipid metabolism has been demonstrated altered in different interstitial lung diseases (ILDs) including idiopathic pulmonary fibrosis (IPF); it can influence the pathogenesis of fibrotic lung disorders. Serum amyloid A (SAA) is an acute phase protein mainly produced by the liver in response to proinflammatory cytokines. Our study compared SAA serum levels in IPF patients to other ILD groups, to explore its potential use as a clinical biomarker. We enrolled 168 patients (40 stable IPF, 8 IPF on acute exacerbation, 30 sarcoidosis, 30 chronic HP, 17 PLCH and LAM, 6 NSIP, 9 UIP-non IPF, 16 SSc-ILD, 6 COPD, 6 other-ILDs, 17 healthy controls), monitored at Siena Regional Centre for ILDs and Saint Anna Hospital at University of Ferrara. IPF patients had higher SAA levels than healthy controls and other patients. We found a cut-off value of SAA (48.84 mcg/ml) which differentiate stable IPF from AE-IPF group. IPF patients have significantly higher SAA serum levels than SSc-ILD with a progressive fibrosis (PPF), indicating that a patient with a progressive fibrosis with serum SAA levels above that cutoff (45,21 mcg/ml) may help to discriminate IPF from other PPFs. ROC curve analysis of SAA levels discriminated cases of IPF from other ILDs, providing evidence of its specificity. SAA is a potential specific biomarker for IPF that can predict clinical course and prognosis of patients. SAA could discriminate an inflammatory ILD from a IPF. SAA could become a potential target for IPF treatment, including via apolipoproteins.